Peran Alat Pendidikan Sebagai Penunjang Pembelajaran - Gita Permata Sari; Hafizah Tulaini; Nadhia Putri Firnanda (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Education has become a human need in everyday life. Through education, humans who initially did not know something become aware of something. In education, things are certainly needed to support it so that the learning objectives can be achieved. One of the supports for achieving learning objectives is educational tools. Educational tools are anything that is used to achieve learning objectives. Educational tools can be in the form of forms or actions. This article will discuss in more depth what educational tools are, the types of educational tools and the role of educational tools in learning.